SIMULASI SISTEM MONITORING OKSIGEN TERLARUT (DO) PADA BUDIDAYA UDANG VANAME BERBASIS INTERNET OF THINGS (IoT) - Hesmi Aria Yanti; Diana Ananda Putri; Siti Zahrotul Fajriyah (Journal of Informatics and Communication Technology (JICT), 2023)
Indonesia has a prospective fishery sector, with an elongated coastline making it potential in the vannamei shrimp farming sector using an Internet of Things (IoT)-based system. Vannamei shrimp (Litopenaeus vannamei) is cultivated with an intensive application of high-density systems with a stocking density of 150 m2, so vannamei shrimp cultivation, namely water quality management to balance the bioenergy metabolism of shrimp, requires water quality such as dissolved oxygen (DO) to increase yields and production. To increase production yields, a system is needed that can monitor dissolved oxygen (DO) levels, an important factor for shrimp growth. The minimum DO level for shrimp growth is 3.0 mg/L, and DO that has the potential to cause mortality is <2.0 mg/L, while the optimal DO value for vannamei shrimp cultivation is >3 mg/L with a tolerance of 2 mg/L. The simulation results of an IoT-based system state that if the green light is on as a sign that the oxygen in the pond has been fulfilled, the results of dissolved oxygen readings are good or normal as seen from the display on the LCD, and the simulation value of the temperature system analysis is seen using ThingsBoard, so that the simulation system can be implemented in real terms.